ANALISIS SEMIOTIKA DARI PUSI “CELANA IBU” KARYA JOKO PINURBO - Yuliana Ana Awa (Parole : Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2021)
This study aims to analyze the semiotic meaning of one of Joko Pinurbo's poems entitled "Celana Ibu." The method used in this study is a qualitative descriptive method. Qualitative descriptive is a method that can analyze, explain, reveal facts, scientific logic and can interpret according to existing data. The main focus of this research is to find out the meaning of the message conveyed by the poet behind the title of the poem. The implementation stage of this research before analyzing the poem "Celana Ibu" is that the researcher reads and understands the contents of the poem as a whole. Furthermore, the markers and markers found were analyzed using the theory of Ferdinand De Saussure. In the study of semiotics, Ferdinand De Saussure's theory is most important to provide signifiers and signifiers (Fanani, 2013). Based on the results of the analysis, "Mother's Pants" are pants made by Mary specifically for her son Jesus. Remembering the story of Jesus at the time of the crucifixion and resurrection wearing no pants. "Mother's Pants" can be interpreted as the most special gift, namely "Prayer" from a mother to facilitate her child's journey to heaven. Because previously, Jesus had been prevented from going to heaven after rising from the dead. That, has not met his mother to give her blessing. The lifting of the poet's meaning and atmosphere from the whole poem is not much different from the story of Jesus and Mary found in the Bible.